Research progress on the use of turning apparatus in long-term bedridden patients (长期卧床患者使用翻身用具的研究进展) - WANG Tianxiu (王天秀); TAO Zhenyan (陶真妍); YU Ping (俞萍); YUAN Yuan (袁媛) (中西医结合护理)
Long-term bed rest may result in skin surface pressure, and primary prevention is to redistribute pressure by turning the patient, therefore reducing the risk of pressure ulcer development. Turning apparatus is designed to help to turn the long-term bedridden patient. This paper introduced several turning apparatuses such as pillow, mattress, a comparison of different apparatuses was also made to provide better choice of turning apparatus for long-term bedridden patients. (患者长期卧床易导致局部皮肤受压, 翻身能够减轻长期卧床患者局部受压的情况, 能有效降低长期卧床患者患压疮的风险。翻身用具对协助卧床患者翻身有积极意义, 本文归纳介绍了近年来临床翻身用具如翻身枕、翻身床垫等的研究进展, 并对各种翻身用具进行比较, 以期为长期卧床患者对翻身用具的选择提供参考。)